Pemberian Aroma Terapi Lavender (Lavandula Angustifolia) Dan Terapi Musik Langgam Jawa Terhadap Kualitas Dan Kuantitas Tidur Lansia Insomnia Berbasis Teori Adaptasi Roy - Wimar Anugrah Romadhon; RR Dewi Rahmawaty (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: Insomnia is a sleep problem that most often occurs in the elderly due to aging. Sleep problems affect the quality and quantity of sleep in the elderly. Lavender aromatherapy and Javanese traditional music is one way to increase the need for sleep. This study aims to analyze the effect of the combination of lavender aromatherapy and Javanese traditional music on sleep quality and quantity of insomniac elderly.Methods: This study design was a quasi-experimental with a pre-test and post-test control group. The number of samples was 36 respondents who were divided into two groups using purposive sampling with inclusion criteria. The independent variable in this study was a combination of lavender aromatherapy and Javanese traditional music, while the dependent variable was the sleep quality and quantity of the insomniac elderly. Data were collected using a structured questionnaire and analyzed using the Wilcoxon Signed Rank Test and Mann Whitney Test with a significance level of 0.05Results: There was an effect of the combination of lavender aromatherapy and Javanese traditional music on sleep quality (p=0.000) and sleep quantity (p=0.001) in the treatment group. The control group there was no effect on sleep quality outcomes (p=0.564) and sleep quantity (p=0.157). The comparison revealed differences in the post test sleep quality (p=0.000) and sleep quantity (p=0.005).Conclusion: The combination of lavender aromatherapy and Javanese traditional music has a significant effect on sleep quality and quantity of insomniac elderly. It is hoped that nursing services will modify this combination of non-pharmacological therapies so as to create more professional and quality nursing services in the health sector.